Performance Measurement of State-Owned Enterprise (BUMN) Bank in Surabaya (Case Study in People's Bank of Indonesia/State-Controlled Bank (Bank BRI) - Utami, Anisa Fitria; Sishadiyati, Sishadiyati; Nisa, Fauzatul Laily (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operating Costs on Operating Income (BOPO) on the profitability of Commercial Banks.  The population used in this study is Bank BRI in 2009-2018.  The data in the study were obtained from the financial statements in 2009-2018.  The analytical method used is multiple linear analysis with the classic assumption test which includes autocorrelation test, multicollinearity test, and heteroscedasticity test using SPSS version 25.0 for windows. The results showed that the variables CAR, NPL, LDR, and OEOI affect the profitability of Bank BRI. The objective of this research is to identify the effect of capital adequacy ratio (CAR), non-performing loan (NPL), loan to deposit ratio (LDR), and operational costs for operating income (BOPO) on commercial bank profitability. People's Bank of Indonesia/State-Controlled Bank (Bank BRI) was utilized as the population for this study from 2009 to 2018. Financial statements from 2009 to 2018 were used to collect data for the study. Multiple linear analysis with classical assumption tests was utilized to conduct the analysis, which included autocorrelation, multicollinearity, and heterocedasticity tests. SPSS version 25.0 for Windows was used to assist with the analysis. The findings indicated that CAR, NPL, LDR, and BOPO all had an effect on the profitability of a People's Bank of Indonesia/State-Controlled Bank (Bank BRI).